Os (dis)cursos do rio: um estudo de história ambiental sobre o rio Meia Ponte na cidade de Goiânia - Pinto, Angela Ciccone (2014)
It is within the city limits of the capital of the State of Goiás that we will make our studies about the relation between man/river. We will, in this way, treat of one of the interfaces of this river in its urban connotation. One will emphasize the movement of influence that the river presents on the interpretation of world by people, its configurations of meaning and the relations of affectivity of goianienses, and, specifically, of the inhabitants of its margins. We intent with this demonstrate "the place and the role of nature in human life" (WORSTER, 1991) correlating large factors linked to the river with expressions of individual senses and meanings. We propose ourselves to identify the wealth and the details of the relation of men with their environment, and also the historical intersections between a river and the regional and global context in which it is inserted within the methodological and theoretical perspective of Environmental History.